Analysis of Gross Regional Domestic Product, Population, and Tourism: How Do They Impact the Regional Original Revenue of Yogyakarta Province? - Zhafira Nasywa Rizky Prasetya; Dewi Wahyu Hapsari (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
This research aims to analyze the effect of Gross Regional Domestic Product (Produk Regional Domestik Bruto/PDRB), population, and tourism sector on the regional original revenue of the Special Region of Yogyakarta. This quantitative research compiled research data that were measured and tested using numerical data. This study used secondary data from the Financial and Asset Management Agency of the Special Region of Yogyakarta Province from 2014 – 2023. The data analysis of this study used SPSS 26 software. The results of this research, with significance value (sig.<0.05), show that PDRB influences the regional original revenue of sig. 0.000 (t= 7.003), the total population influences the regional original revenue of sig. 0.003 (t=4.970), and the tourism sector influences the regional original revenue of sig. 0.003 (t=4.807). The coefficient of determination shows that (R2 =0.638) which means that the effect of PDRB, population, and tourism on the regional original revenue of the Special region of Yogyakarta Province is 63.8%. In conclusion, increasing regional original revenue can be achieved and succeeded by stimulating economic growth, managing population growth, and optimally developing the potential of the tourism sector. Those efforts can be a foundation for regional governments in designing sustainable and competitive economic development policies.